2019
DOI: 10.1107/s1600576719006381
|View full text |Cite
|
Sign up to set email alerts
|

Protein crystal structure determination with the crystallophore, a nucleating and phasing agent

Abstract: Obtaining crystals and solving the phase problem remain major hurdles encountered by bio-crystallographers in their race to obtain new high-quality structures. Both issues can be overcome by the crystallophore, Tb-Xo4, a lanthanide-based molecular complex with unique nucleating and phasing properties. This article presents examples of new crystallization conditions induced by the presence of Tb-Xo4. These new crystalline forms bypass crystal defects often encountered by crystallographers, such as low-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 61 publications
0
49
0
Order By: Relevance
“…7 In our previous work, native tFprA structure was solved under aerobic condition with a crystallophore derivative. 19 In contrast, the first crystal structure of this report presents tFprA (tFprA anox ) was obtained in strict anaerobic conditions after native purification. The second structure was obtained aerobically in the presence of 125 bars of Kr and is refered to as tFprA oxo-Kr .…”
mentioning
confidence: 84%
“…7 In our previous work, native tFprA structure was solved under aerobic condition with a crystallophore derivative. 19 In contrast, the first crystal structure of this report presents tFprA (tFprA anox ) was obtained in strict anaerobic conditions after native purification. The second structure was obtained aerobically in the presence of 125 bars of Kr and is refered to as tFprA oxo-Kr .…”
mentioning
confidence: 84%
“…A terbium complex, called crystallophore N • 1 or Tb-Xo4, with phasing and nucleating properties was recently described [19,20,27]. When preparing lysozyme solutions in pure milliQ water including 10 mM Tb-Xo4 for screening experiments, we observed that the addition of the compound led to the formation of a pellet composed of single lysozyme crystals at the bottom of Eppendorf tubes after 20 to 30 days in the cold room.…”
Section: Tracking the Nucleant Effect Of The Crystallophore Tb-xo4on mentioning
confidence: 83%
“…PitA Chy crystals were soaked for 20 min in mother liquor containing 100 mM Tb-Xo4 (Polyvalan Crystallophore No. 1, Molecular Dimensions; Engilberge et al, 2017Engilberge et al, , 2019 to prepare a terbium-derivatized crystal form (PitA ChyTb ).…”
Section: Crystallizationmentioning
confidence: 99%